THE REFLECTION OF NATIONAL CULTURE AND MENTALITY IN PROVERBS AND SAYINGS (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2024)
Proverbs and sayings, deeply rooted in a nation's collective wisdom and experience, offer a powerful lens through which to understand its cultural and mental landscape. This article explores the multifaceted ways in which proverbs and sayings reflect the values, beliefs, and perspectives of a particular nation. Through a comparative analysis of proverb collections from diverse cultures, the study examines how these concise expressions encapsulate social norms, historical experiences, religious influences, and prevailing attitudes towards life, work, and relationships.